2012
DOI: 10.1002/ijc.27522
|View full text |Cite
|
Sign up to set email alerts
|

Pesticide use, immunologic conditions, and risk of non‐Hodgkin lymphoma in Canadian men in six provinces

Abstract: Pesticide exposures and immune suppression have been independently associated with the risk of non-Hodgkin lymphoma (NHL), but their joint effect has not been well explored. Data from a case-control study of men from six Canadian provinces were used to evaluate the potential effect modification of asthma, allergies, or asthma and allergies and hay fever combined on NHL risk from use of: (i) any pesticide; (ii) any organochlorine insecticide; (iii) any organophosphate insecticide; (iv) any phenoxy herbicide; (v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
2
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 21 publications
0
21
2
1
Order By: Relevance
“…Two papers reported results from the Cross-Canada Study of Pesticides and Health, which was a case control study conducted in six Canadian provinces [43,47]. Population based controls were frequency matched to NHL cases, diagnosed 1991–1994, based on age and province of residence.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two papers reported results from the Cross-Canada Study of Pesticides and Health, which was a case control study conducted in six Canadian provinces [43,47]. Population based controls were frequency matched to NHL cases, diagnosed 1991–1994, based on age and province of residence.…”
Section: Resultsmentioning
confidence: 99%
“…The questionnaires used for this study were based on the one used in the USA National Cancer Institute led case-control studies [20,23,30,56,59,60] in Nebraska [18,58] and Kansas [34]. McDuffie et al [43] and Pahwa et al [47] present results from some of the same analyses with the same population. When the same analysis was reported in both papers we selected the effect estimate from the paper by Pahwa et al [47] because the authors excluded four NHL cases based on pathology review that occurred subsequent to the analyses reported in McDuffie et al [43].…”
Section: Resultsmentioning
confidence: 99%
“…128 In yet another article from the 6 Canadian provinces study, the joint effect of pesticide exposure and immune suppression was preliminarily evaluated. 61 Study participants with asthma or hay fever had nonsignificantly elevated risks of NHL associated with the use of MCPA (OR, 2.67; 95% CI, 0.90-7.93) compared with participants without any of these conditions (OR, 0.81; 95% CI, 0.39-1.70).…”
Section: Prostate Cancermentioning
confidence: 88%
“…A recent AHS analysis of male applicators found null associations with malathion use and NHL risk overall 18. Additionally, some case–control studies have shown a positive association for malathion use and NHL 9 46 47. Adjustment for other variables shown to be associated with NHL risk in farming populations, including whether or not our study participants grew up on a farm, their self-reported history of physician diagnosed allergies and contact with farm animals, did not alter the relationships in our study.…”
Section: Discussionmentioning
confidence: 99%